Vascular Endothelial Growth Factor and Brain-Derived Neurotropic Factor Levels in Ischemic Stroke Subject - Andri Hidayat; Mansyur Arief; Andi Wijaya; Suryani As'ad (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Vascular endothelial growth factor (VEGF) and brain-derived neurotropic factor (BDNF) present during early neuronal development and play important roles in the process of neurorepairing includes angiogenesis, neurogenesis and neuronal plasticity after ischemic stroke. In this study, we observed VEGF and BDNF levels of subjects with ischemic stroke in different onset time.METHODS: A cross sectional study was designed. Study subjects were 51 ischemic stroke subjects, aged 30-80 years old, recruited from Gatot Subroto Army Central Hospital, Jakarta, Indonesia. Ischemic stroke was diagnosed by neurologist, based on clinical examination and magnetic resonance imaging (MRI) result. Subjects were divided into 3 groups based on onset time of stroke: <7 days (group A), 7-30 days (group B) and >30 days (Group C). VEGF and BDNF levels from serum were measured using lumine Magpix. The data was analyzed for comparison and correlation.RESULTS: VEGF and BDNF levels of group B and C were significantly different with p=0.034 and p=0.007, respectively. Group B had the highest VEGF levels, whereas Group C had the highest BDNF level. VEGF and BDNF levels in each group were not significantly correlated.CONCLUSION: Each stage of time after ischemic stroke has different recovery activities like angiogenesis, neurogenesis and plasticity. Angiogenesis process was optimum in 7-30 days after onset. in more than 30 days onset, Low VEGF with high BDNF have important role in a long period of time after the onset of stroke in the regeneration and repair, such as maintaining neuronal survival and plasticity.KEYWORDS: ischemic stroke, VEGF, BDNF